Greater topoclimatic control of above‐ versus below‐ground communities. (27th September 2020) - Mod, Heidi K.; Scherrer, Daniel; Di Cola, Valeria; Broennimann, Olivier; Blandenier, Quentin; Breiner, Frank T.; Buri, Aline; Goudet, Jérôme; Guex, Nicolas; Lara, Enrique; Mitchell, Edward A. D.; Niculita‐Hirzel, Hélène; et al.
Abstract: Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1, 500 taxa and phylotypes along a c. 3, 000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems. Abstract : The degree to which climate controls the distributions of taxa affects future ecosystems. Including both above‐ and below‐ground organisms, we compare topoclimatic control on >1, 500 taxa by fitting SDMs. Differences in model performances suggest that the influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil conditions are likely more important for soil microbiota. Future scenarios of soil microclimate and microhabitats, together with ecologically dependent biota, are thus needed to understand and realistically forecast the future ecosystems.